Ordering behavior in a newsstand experiment (2018)
We study ordering behavior in a multi-item newsvendor problem with resource constraints (the newsstand problem). We run a laboratory experiment of a newsstand problem with 95 undergraduate students, using a two-product portfolio while manipulating a budget constraint according to Abdel-Malek and Montanari (2005a)'s newsstand problem analysis. We observe level and poor demand chasing behaviors, as documented in newsvendor experiments. We also observe that more budget availability favors profit performance for a high profitability item and service level performance for a low profitability item. These results are supported by estimates of how participants assess leftover and shortage costs as well as their willingness to pay for additional resources. The results also highlight the role that service level preferences and the tradeoff between increased resources and profit performance play in ordering decisions. We discuss implications for inventory management and behavioral experiments of ordering problems. © 2017 Elsevier B.V.